2019
DOI: 10.1073/pnas.1813181116
|View full text |Cite
|
Sign up to set email alerts
|

Processing generates 3′ ends of RNA masking transcription termination events in prokaryotes

Abstract: Two kinds of signal-dependent transcription termination and RNA release mechanisms have been established in prokaryotes in vitro by: (i) binding of Rho to cytidine-rich nascent RNA [Rho-dependent termination (RDT)], and (ii) the formation of a hairpin structure in the nascent RNA, ending predominantly with uridine residues [Rho-independent termination (RIT)]. As shown here, the two signals act independently of each other and can be regulated (suppressed) by translation–transcription coupling in vivo. When not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(102 citation statements)
references
References 42 publications
(47 reference statements)
2
99
1
Order By: Relevance
“…These results thus suggest that the 5 portion of the galETKM mRNA after the RNase E cleavages is removed immediately, possibly by 3 →5 exoribonucleases, as has been demonstrated in many previous studies (Mott et al, 1985;Belasco et al, 1986;Hui et al, 2014;Wang et al, 2019).…”
Section: The 5 Portion Mrna Generated By Rnase E Cleavage Is Degradedsupporting
confidence: 82%
See 4 more Smart Citations
“…These results thus suggest that the 5 portion of the galETKM mRNA after the RNase E cleavages is removed immediately, possibly by 3 →5 exoribonucleases, as has been demonstrated in many previous studies (Mott et al, 1985;Belasco et al, 1986;Hui et al, 2014;Wang et al, 2019).…”
Section: The 5 Portion Mrna Generated By Rnase E Cleavage Is Degradedsupporting
confidence: 82%
“…In the RIT o 2 mutant, two bases from the bottom of the stem of the terminator hairpin are substituted to their complementary bases ( Figure 1C). In the RIT o 2 mutant, the function of the terminator hairpin in the blockage of 3 → 5 exoribonuclease was impaired (Wang et al, 2019). When RNA from the RIT o 2 mutant was analyzed using the M-probe, we confirmed that the mutations caused the shortening of the galETKM mRNA by about 100 nucleotides and also decreased the galETKM amount to about 40% of the wild type (WT; lane 2 in Figure 1D; Wang et al, 2019).…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations